Abundance and Monthly Frequency of Phlebotomine Sand Flies (Diptera: Phlebotominae) in Some Municipalities in the State of Rio de Janeiro, Brazil - Azevedo, Alfredo Carlos Rodrigues de; Andrade-Coelho, Cláudia Alves de; Silva, Vanderlei Campos da; Sena, Caroline Almeida Pereira; Souza, Filipe Jonas Mattos Soares de; Souza, Nataly Araujo de (EntomoBrasilis, 2015)
Abstract. The present study had the objective of estimating the abundance and monthly frequency of vector phlebotomines for American cutaneous leishmaniasis (ACL) in the municipalities of Saquarema, Rio Bonito, Piraí and Rio Janeiro, in the state of Rio de Janeiro. Seven sites located in these municipalities were monitored over a 10 to 12-month period. Lutzomyia migonei (França) Lutzomyia (Pintomyia) fischeri (Pinto) and Lutzomyia (Nyssomyia) intermedia (Lutz & Neiva) the vectors for ACL, were recorded in all four of these municipalities. In this study, it was noteworthy that Lutzomyia (Lutzomyia) longipalpis (Lutz & Neiva) the vector of visceral leishmaniasis (VL) was registered. In addition to these vectors, three other phlebotomine species, including Lutzomyia edwardsi (Mangabeira), Lutzomyia sallesi (Galvão & Coutinho) and Lutzomyia firmatoi (Barreto, Martins & Pellegrino) were captured in peridomestic environments at the seven monitoring sites (MS) over a 1476-hour period. A total of 23,187 specimens were captured leishmaniasis vector species accounted for 99.6% of the specimens captured. Lutzomyia (N.) intermedia presented the highest abundance (SISA = 1.0) and was recorded at all monitoring sites, with the highest mean Williams values. Lutzomyia migonei was the second most abundant and was found at all sites except MS6 (SISA = 0.66). Lutzomyia (L.) longipalpis, Lutzomyia sallesi, Lutzomyia firmatoi and Lutzomyia (P.) fischeri were occasionally observed at the MS. These studies point to the need for adoption of policies involving actions of health education, associated with the notion of environmental management and the basics concepts of the disease, as element of success of an integrated program of entomological surveillance and control of American cutaneous leishmaniasis. Abundância e Frequência Mensal de Flebotomíneos (Diptera: Phlebotomiae) em Alguns Municípios do Estado do Rio de Janeiro, Brasil Resumo. O presente estudo teve o objetivo de estimar a abundância e frequência mensal de algumas espécies de flebotomíneos incriminados como vetores da Leishmaniose Tegumentar Americana (LTA), nos municípios de Saquarema, Rio Bonito, Piraí e Rio Janeiro, no Estado do Rio de Janeiro. Sete sítios localizados nesses municípios foram monitorados ao longo de um período de 10 a 12 meses. Lutzomyia migonei (França), Lutzomyia (Pintomyia) fischeri (Pinto) e Lutzomyia (Nyssomyia) intermedia (Lutz & Neiva), foram registrados em todos os quatro municípios. Lutzomyia (Lutzomyia) longipalpis (Lutz & Neiva) vetor comprovado da Leishmaniose Visceral (LV), foi registrado. Além desses vetores, outras três espécies de flebotomíneos, incluindo Lutzomyia edwardsi (Mangabeira), Lutzomyia sallesi (Galvão & Coutinho) e Lutzomyia firmatoi (Barreto, Martins & Pellegrino) foram capturados em ambiente domiciliar nos sete sítios de monitoramento (SM) durante um período de 1.476 horas totalizando 23.187 espécimes. Espécies responsáveis pela transmissão das leishmanioses totalizaram 99,6%. L. (N.) intermedia apresentou a maior abundância (SISA = 1,0) e foi registrada em todos os SM, com os maiores valores médios de captura. Lutzomyia migonei foi a segunda mais abundante e também foi encontrada em todos os locais, exceto MS6 (SISA = 0,66). Lutzomyia (L.) longipalpis, Lutzomyia sallesi, Lutzomyia firmatoi e Lutzomyia (P.) fischeri foram ocasionalmente observadas nas SM. Esses estudos apontam para a necessidade de adoção de políticas que envolvam ações de educação em saúde, associados à noção de manejo ambiental e conceitos básicos da doença, como elemento de sucesso de um programa integrado de vigilância entomológica e controle da LTA.